Study on the vertical component of lightning electric field during monsoon period in Malaysia - Salimi, Behnam (Trans Tech, 2014)
The most recognized and powerful demonstration of electrostatics in the natural world is a lightning discharge. The misoperation of several equipment and circuits would not only be caused by a direct contact with the lightning flash, but also by an indirect effect of a lightning channel. Appropriate information about lightning signature parameters can provide precise knowledge of lightning discharge that can be essential for the design of more improved detection and protective system. In this paper, the preliminary breakdown pulse train and the first return stroke of cloud to ground lightning discharge signatures observed in south of Malaysia are analyzed. Statistical analyses of the ratio between the maximum preliminary breakdown pulse trains amplitude and the first return stroke amplitude (BP/RS ratio), and the time duration between the high active part of the pulse train, and the return stroke (BP/RS separation) are presented. Observations on the statistical analyses show that about 94% of lightning signals have detectable breakdown pulses. The arithmetic means of BP/RS ratio and the BP/RS separation are 36.3% and 26.4ms, respectively.